2013
DOI: 10.1590/0074-0276108022013011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of amodiaquine on paired Schistosoma mansoni adult worms at concentrations of less than 5 µg/mL

Abstract: In this study, the in vitro effects of amodiaquine (AQ)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Given that S. japiconium eggs are virtually spineless, it is unlikely that the schistosome spine plays a major function. In fact, a recent report comparing egg morphology between Praziquantel resistant and susceptible S. mansoni infection suggests that the spine actually hinders egg transit (47). More specifically, resistant strain eggs were shown to have smaller lateral spines than susceptible strain eggs, and were also more frequently shed into host feces (47).…”
Section: Endothelial Extravasationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that S. japiconium eggs are virtually spineless, it is unlikely that the schistosome spine plays a major function. In fact, a recent report comparing egg morphology between Praziquantel resistant and susceptible S. mansoni infection suggests that the spine actually hinders egg transit (47). More specifically, resistant strain eggs were shown to have smaller lateral spines than susceptible strain eggs, and were also more frequently shed into host feces (47).…”
Section: Endothelial Extravasationmentioning
confidence: 99%
“…In fact, a recent report comparing egg morphology between Praziquantel resistant and susceptible S. mansoni infection suggests that the spine actually hinders egg transit (47). More specifically, resistant strain eggs were shown to have smaller lateral spines than susceptible strain eggs, and were also more frequently shed into host feces (47). Thus, from an evolutionary standpoint, perhaps S. japiconium has taken advantage of spine absence.…”
Section: Endothelial Extravasationmentioning
confidence: 99%
“…Furthermore, the one-day exposure to AQ also induced the specific alterations (severe swelling and/or localization of hemozoin) in the male and female adult worms at 5 and 10 μg/ml. The alterations were the same as those caused by continuous exposure to AQ [ 9 ]. With subsequent incubation in drug-free media, all the female worms maintained the AQ-specific morphological damage during the 14-day incubation period, while the male worms gradually regained their normal appearance.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, Oliver et al showed that chloroquine [ 14 ], one of the 4-aminoquinoline derivatives similar in structure to AQ, exerted antischistosomal activities by inhibiting the formation of hemozoin, a detoxification product of free haem metabolized from haemoglobin. Similarly, it has been surmised that the free haem caused by AQ may be responsible for damaging the reproductive system of female worms and inducing the specific morphological alterations of male and female worms [ 9 ]. The differences in the mode of action of AQ and PZQ are thought to contribute to differences in the specific morphological alterations caused by the two drugs, as well as in the onset of morphological alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation